A Study of Nonlinear Vibration of Euler-Bernoulli Beams Using Coupling Between The Aboodh Transform And The Homotopy Perturbation Method - Bera, PK; Das, SK; Bera, P (International Journal of Computer Sciences and Engineering, 2025)
Aboodh transform (AT) in combination with the homotopy perturbation method (HPM) is employed to solve the nonlinear differential equation of motion for Euler-Bernoulli beams in a unified way. Aboodh transform based homotopy perturbation method (ATHPM) is found to give analytic solutions with all perturbative corrections to both the displacement and the oscillation frequency in a very simple and straight forward manner. Here, we have also demonstrated the sophistication and simplicity of this technique.